(untitled) (Physical Education, Health and Social Sciences, 2026)
Mosquitoes are blood suckers that bite mammals, birds, reptiles, amphibians, and fish to transmit diseases like filariasis, malaria, and dengue fever. Various factors, including climate, water sources, vegetation, land use, and human activities, contribute to the diversity of mosquitoes in an area. This study aimed to assess mosquito diversity and their habitat preference in the Tank district, Khyber Pakhtunkhwa. The study was conducted from November 2024 to May 2025, resulting in a wide-ranging and representative sample. A total of 10 study sites with seven different habitats were selected for mosquito sampling, including marshy areas, sewage, crops, agriculture, animal sheds, ponds, and barren land. Sampling was done using sweep nets and inhalation mosquito lamps (IML). Furthermore, the sampling was preserved in a 95% ethanol solution. The collected samples were identified with the help of taxonomic keys, examined using a stereo-zoom microscope. A total of 13 species were identified. Out of the thirteen recorded species, seven were included in the Anophelinae and Culicinae, two were from the tribe Aedini, and four were from the Culicini. The most prevalent species identified was Culex quinquefasciatus, while Aedes albopictus, a primary vector for dengue fever, was the least common. A high and diversified population was recorded in cropland. These results highlight the diverse mosquito populations within the region and underscore the need for ongoing surveillance and vector control efforts to mitigate the health risks posed by these species. Appropriate monitoring steps should be taken to prevent the further growth of the mosquito population; otherwise, it may lead to the spread of diseases such as malaria and Dengue fever.